Ion accumulation, water relations and osmotic adjustment in Atriplex argentina, A. crenatifolia, A. lampa and A. nummularia under saline conditions - Barcena, Nadia (2016)
Salinity is a major stress that adversely affects growth and productivity in plants. There are species that tolerate this stress within the genus Atriplex. Four species, A. lampa, A. crenatifolia, A. nummularia and A. argentina were compared for their ion accumulation and water relations under saline conditions. A greenhouse study was conducted by irrigating the four species with NaCl solutions at concentrations 0%, 1%, 2% and 4% starting when plants were six months old. Plants were harvested 45 d after starting the salinity treatments and analyzed for their ion contents. In the four Atriplex species, Na+ and Cl–contents in plants increased, while Ca2+ and Mg2+ decreased with the increase of salinity in the irrigation solution. The results suggested that A. argentina and A. nummularia were able to maintain a higher leaf relative water content (RWC) at low leaf water potential, which was associated with a greater capacity of osmotic adjustment. A. lampa showed lower ion accumulation and minor osmotic adjustment than the other species. It can be concluded that the accumulation of ions favors the lower osmotic potential and contributes to osmotic adjustment in these halophytes.